Randomised comparison of the LMA Supreme (TM) with the I-Gel (TM) in spontaneously breathing anaesthetised adult patients - Chew, E.F.F.; Hashim, N.H.M.; Wang, C.Y. (Australian Soc Anaesthetists, 2010)
We compared the performance of the LMA Supreme (TM) (SLMA) with the I-Gel (TM) during anaesthesia in spontaneously breathing adult patients Ninety patients with American Society of Anesthesiologists physical status I or II were studied in a prospective randomised controlled study Our primary outcome measure was oropharyngeal leak pressure We also compared the overall insertion success rate, ease of insertion, adequacy of ventilation and incidence of complications The mean (SD) oropharyngeal leak pressure for the SLMA was 25 6 (5 1) cmH(2)O, which was greater than for the I-Gel 20 7 (5 9) cmH(2)O (P=0 0001) The first attempt and overall insertion success rates were similar between the two groups (SLMA 978 and 978%, I-Gel 93 3 and 100%, P=0 132) The SI-MA was rated easier to Insert than the I-Gel (P=0 011), but the time taken for insertion (P=0 433) was similar The incidence of complications was low in both groups The grade of fibreoptic view was better with the I-Gel than the SLMA (P=0 001) We conclude that in adults with normal airways, the SLMA is easier to insert and provides a higher oropharyngeal leak pressure but fibreoptic views are better with the i-gel